Pharmacokinetic Effects of Isavuconazole Coadministration With the Cytochrome P450 Enzyme Substrates Bupropion, Repaglinide, Caffeine, Dextromethorphan, and Methadone in Healthy Subjects. Issue 1 (15th July 2016) - Yamazaki, Takao; Desai, Amit; Goldwater, Ronald; Han, David; Howieson, Corrie; Akhtar, Shahzad; Kowalski, Donna; Lademacher, Christopher; Pearlman, Helene; Rammelsberg, Diane; Townsend, Robert
Abstract: This report describes phase 1 clinical trials performed to assess interactions of oral isavuconazole at the clinically targeted dose (200 mg, administered as isavuconazonium sulfate 372 mg, 3 times a day for 2 days; 200 mg once daily [QD] thereafter) with single oral doses of the cytochrome P450 (CYP) substrates: bupropion hydrochloride (CYP2B6; 100 mg; n = 24), repaglinide (CYP2C8/CYP3A4; 0.5 mg; n = 24), caffeine (CYP1A2; 200 mg; n = 24), dextromethorphan hydrobromide (CYP2D6/CYP3A4; 30 mg; n = 24), and methadone (CYP2B6/CYP2C19/CYP3A4; 10 mg; n = 23). Compared with each drug alone, coadministration with isavuconazole changed the area under the concentration‐time curves (AUC∞ ) and maximum concentrations (Cmax ) as follows: bupropion, AUC∞ reduced 42%, Cmax reduced 31%; repaglinide, AUC∞ reduced 8%, Cmax reduced 14%; caffeine, AUC∞ increased 4%, Cmax reduced 1%; dextromethorphan, AUC∞ increased 18%, Cmax increased 17%; R‐methadone, AUC∞ reduced 10%, Cmax increased 3%; S‐methadone, AUC∞ reduced 35%, Cmax increased 1%. In all studies, there were no deaths, 1 serious adverse event (dextromethorphan study; perioral numbness, numbness of right arm and leg), and adverse events leading to study discontinuation were rare. Thus, isavuconazole is a mild inducer of CYP2B6 but does not appear to affect CYP1A2‐, CYP2C8‐, or CYP2D6‐mediated metabolism.